Korelasi sikap ibu dengan pemberian ASI eksklusi - Sitio, Nelly Juwita; Siregar, Farida Linda Sari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Breast milk is an emulsion of fat in a solution of protein, lactose and inorganic salts which is secreted by the mother's mammary glands and is useful as food for her baby. Breast milk contains immune substances that protect children from infections and chronic diseases and reduce the possibility of suffering from diabetes, asthma, obesity and other diseases in the future. According to the World Health Organization (WHO), Indonesia's exclusive breastfeeding coverage in 2022 was recorded at only 67.96%, down from 69.7% in 2021. Various factors influence knowledge about exclusive breastfeeding, including mother's knowledge, age, education level, parity, and information provided by health workers. Purpose: To determine the correlation between maternal attitudes and exclusive breastfeeding. Method: A cross-sectional quantitative study was conducted at the Integrated Service Unit of Tomuan Health Center in October 2023 - June 2024. The number of samples was 57 respondents collected using total sampling with inclusion criteria, namely mothers with children aged 6-24 months. The procedure for implementing data collection during the immunization schedule every Monday and at the toddler integrated service post schedule was carried out. The instrument in this study used a questionnaire containing questions regarding the level of mother's knowledge about providing exclusive breastfeeding to infants. Results: The majority of respondents were aged 34-38 years (33.3%), 37 respondents (61.4%) had a high school/vocational education, and 37 (64.9%) worked as housewives with family income <2.8 million/month. The majority of respondents had 1-2 children as many as 31 respondents (54.4%), as many as 56 respondents (98.2%) had received information about exclusive breastfeeding from health workers, had a positive attitude as many as 50 respondents (87.7%), and provided exclusive breastfeeding as many as 45 (78.9%). The results of the data test between the maternal attitude variable and exclusive breastfeeding obtained a p-value of 0.000, meaning that there is a significant relationship between the two variables. Conclusion: There is a significant relationship between maternal attitudes and exclusive breastfeeding for babies. This shows that the more positive the mother's attitude, the better the mother will be at providing exclusive breast milk to their babies. Keywords: Baby; Breastfeeding Mothers; Exclusive Breastfeeding. Pendahuluan: Air Susu Ibu (ASI) merupakan suatu emulsi lemak dalam larutan protein, laktosa, dan garam-garam anorganik yang disekresi oleh kelenjar mammae ibu dan bermanfaat sebagai makanan bagi bayinya. ASI mengandung zat-zat kekebalan yang melindungi anak dari infeksi dan penyakit kronis serta mengurangi kemungkinan menderita diabetes, asma, obesitas, dan penyakit lainnya di kemudian hari. Menurut World Health Organization (WHO), cakupan ASI eksklusif Indonesia pada 2022 tercatat hanya 67.96%, turun dari 69.7% pada 2021. Berbagai faktor memengaruhi pengetahuan tentang pemberian ASI eksklusif, termasuk pengetahuan ibu, usia, tingkat pendidikan, paritas, dan informasi yang diberikan oleh tenaga kesehatan. Tujuan: Untuk mengetahui korelasi sikap ibu dengan pemberian ASI eksklusi. Metode: Penelitian kuantitatif cross sectional, dilakukan di UPT Puskesmas Tomuan pada bulan Oktober 2023 - Juni 2024. Jumlah sampel sebanyak 57 responden yang dikumpulkan menggunakan total sampling dengan kriteria inklusi, yakni ibu dengan memiliki anak di rentang usia 6-24 bulan. Prosedur pelaksanaan pengambilan data pada saat jadwal imunisasi di tiap hari senin dan pada jadwal posyandu balita dilakukan. Instrumen pada penelitian ini menggunakan kuesioner berisi pertanyaan yang mengenai tingkat pengetahuan ibu tentang pemberian ASI eksklusif pada bayi. Hasil: Mayoritas responden berusia 34-38 tahun (33.3%), pendidikan terakhir SMA/SMK sebanyak 37 responden (61.4%), dan bekerja sebagai ibu rumah tangga sebanyak 37 (64.9%) dengan pendapatan keluarga <2.8 juta/bulan. Mayoritas responden memiliki 1-2 anak sebanyak 31 responden (54.4%), sebanyak 56 responden (98.2%) pernah mendapatkan informasi tentang ASI eksklusi dari tenaga Kesehatan, memiliki sikap positif sebanyak 50 responden (87.7%), dan memberikan ASI eksklusif sebanyak 45 (78.9%). Hasil uji data antara variabel sikap ibu dan pemberian ASI eksklusif mendapatkan p-value 0.000, artinya terdapat hubungan yang signifikan antara kedua variabel tersebut. Simpulan: Terdapat hubungan yang signifikan antara sikap ibu dengan pemberian ASI eksklusi pada bayi. Hal ini menunjukkan semakin positif sikap yang dimiliki ibu, maka semakin baik pula ibu dalam memberikan ASI eksklusi pada bayi mereka. Kata Kunci: ASI Eksklusif; Bayi; Ibu Menyusui.